6(7x+9)=264

Simple and best practice solution for 6(7x+9)=264 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(7x+9)=264 equation:


Simplifying
6(7x + 9) = 264

Reorder the terms:
6(9 + 7x) = 264
(9 * 6 + 7x * 6) = 264
(54 + 42x) = 264

Solving
54 + 42x = 264

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-54' to each side of the equation.
54 + -54 + 42x = 264 + -54

Combine like terms: 54 + -54 = 0
0 + 42x = 264 + -54
42x = 264 + -54

Combine like terms: 264 + -54 = 210
42x = 210

Divide each side by '42'.
x = 5

Simplifying
x = 5

See similar equations:

| 6(3+k)=48 | | c-(-75)=25 | | -250+5(3)= | | 4(h+8)=16 | | 6-4u=2 | | a(6a^2+2a+9)= | | 6(2-x)=20 | | 21-11y=7 | | 2x-10(2x-1)=5 | | 0.5x+58=-23 | | 7y=210 | | -6x-7=29 | | 250=x*1000 | | 6x+2x-5=43 | | (X-3)(X+3)=6x^2-14 | | 5+3(4x-2)=-18 | | a+7=11 | | 16R+4R+80=X | | -2x^4(6x^3-5x+5)= | | 790=7.5x+(197.5+(-1.875x)) | | 9+2(b-8)=9(-3-2b) | | 5p=16-3p | | 6-x+2x=3x | | 3(6y-6)-(2y+7)= | | 1.5=x*11 | | 5e-14=8 | | 4n(-n^3-4n+1)= | | 8-2(2x-5)=6 | | -24+w-8=4 | | 3z-2z=8 | | 3x^2-2x=5x+1 | | 7x^2+5x-16=0 |

Equations solver categories